The constitutional rights of indigenous beliefs adherents in minority fiqh perspective - Gugun El Guyanie; Aji Baskoro (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
Indigenous Beliefs Adherents (Penghayat Kepercayaan) who were victims of injustice filed a judicial review and finally brought out to Constitutional Court Decision Number 97/PUU-XIV/2016. This decision became the legal basis for Indigenous Beliefs Adherents to obtain their constitutional rights: recognition, respect, and protection by embedding the beliefs they believe in on the electronic ID card (e-KTP). This study aims to analyze based on the epistemology of minority fiqh on the constitutional rights of Indigenous Beliefs Adherents. In contrast to many studies that place minority fiqh in defense of Muslim minorities in the West, this study develops minority fiqh for non-Muslim minorities in Muslim-majority countries. This article uses normative legal research, with qualitative descriptive analysis with a case approach that analyzes Constitutional Court Decision Number 97/PUU-XIV/2016. The study results show that the Constitutional Court Decision viewed from the perspective of minority fiqh is very relevant. Because the purpose of Islamic law is none other than to protect minorities, including freedom of religion. Minority fiqh is also in line with the concept of constitutional rights. The Constitutional Court Decision restores Indigenous Beliefs' constitutional rights to the same level as other religious groups.